(untitled) (International Journal of Ayurveda and Pharma Research, 2016)
Nosocomial infection (NI), also known as hospital-acquired infections, has had increased attention due to the significant morbidity and mortality caused by NI worldwide. Transmission of NI is believed to occur predominantly via the mode of pathogen exchange to and from contaminated hands. Thus, maintaining clean and microbe free hands gains a lot of scientific and clinical scope. Accordingly, hand hygiene techniques (using hand sanitizers particularly) to eliminate disease-causing microbial bugs have been considered one of the primary-most infection blocking methods. Several scientific studies have validated the clinical efficacy of hand sanitizers against the most commonly involved microbial strains in the pathogenesis of NI. The goal of this study was to evaluate the bactericidal activity of the study material Clean Hand Gel, a specialized herbal hand sanitizer with bio-actives enriched with the goodness of Camphor, Cumin seeds, Vetiver, Citrus and Neem. The study material was evaluated for its bactericidal activity against the specified microorganisms (Bacteria - Staphylococcus aureus, Pseudomonas aeruginosa, Escherichia coli and Enterococcus hirae species) by time kill assay. Data indicated that the tested product at 20% concentration when tested for 120 seconds of contact time against specified bacterial species resulted in considerable logarithmic reductions of 0.03, 0.125, 0.097 and 0.091 in the bacterial viable counts of Staphylcoccus aureus, Pseudomonas aeruginosa, Escherichia coli and Enterococcus hirae, respectively. It can be concluded that InnoVisions Clean Hand Gel with its tested in vitro effects against clinically important NI causing bacterial organisms S. aureus, P. aeruginosa, E. coli and E. hirae, can be used as an effective herbal hand sanitizer in controlling the transmission of disease causing microorganisms (specified bacteria) from hand to hand and can have potential implications in controlling measures against the spread of associated diseases.